Misterchef? Cooks, Chefs and Gender in MasterChef Australia - Herkes Ellen; Redden Guy (Open Cultural Studies, 2017)
MasterChef Australia is the most popular television series in Australian history. It gives a wide range of ordinary people the chance to show they can master culinary arts to a professional standard. Through content and textual analysis of seven seasons of the show this article examines gendered patterns in its representation of participants and culinary professionals. Women are often depicted as home cooks by inclination while the figure of the professional chef remains almost exclusively male. Despite its rhetoric of inclusivity, MCA does little to challenge norms of the professional gastronomic field that have devalued women’s cooking while valorising “hard” masculinized culinary cultures led by men.